PENGARUH E-MODUL MATEMATIKA TERHADAP HASIL BELAJAR DAN MOTIVASI SISWA SEKOLAH DASAR - Ana Nur Hidayah; Sri Sumartiningsih; Sri Wardani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to systematically examine the effect of the use of mathematics e-modules on student learning outcomes and motivation at the elementary school level through a literature review. The method used is a Systematic Literature Review (SLR) by analyzing relevant scientific journal articles within a certain time period. The results of the review indicate that mathematics e-modules, especially those designed interactively and contextually, have significant potential to improve student learning outcomes because they present more engaging, personalized material and provide instant feedback. In addition, student motivation also tends to increase due to the multimedia elements and ease of access offered by e-modules. In conclusion, mathematics e-modules are highly recommended as innovative teaching materials for mathematics learning in elementary schools to optimize student learning outcomes and motivation.